2020
DOI: 10.1155/2020/8179795
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of the Quality Assurance, Quality Control, and Testing in the Shiraz Cohort Heart Study

Abstract: To determine the conclusive integrity in the Shiraz Cohort Heart Study (SCHS) project, management began quality assurance (QA) and quality control (QC) of the collected data throughout the study end-points. The QA is a focused process that prevents and detects data collection errors and verification of intended requirements in the SCHS. The QC is a subset of QA intended to capture errors in processing data through testing and preventive processes to identify problems, defects, or intended requirements. SCHS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Additionally, 22.1% of the Shiraz cohort study population demonstrated intermediate-risk scores, while 3.4% showed high-risk scores. However, 13.2% and 2.5% of participants in our study, respectively, exhibited intermediate or high-risk scores (Table 5 ), indicating that Shiraz University employees are potentially less likely to develop ASCVD ( P < 0.001) [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, 22.1% of the Shiraz cohort study population demonstrated intermediate-risk scores, while 3.4% showed high-risk scores. However, 13.2% and 2.5% of participants in our study, respectively, exhibited intermediate or high-risk scores (Table 5 ), indicating that Shiraz University employees are potentially less likely to develop ASCVD ( P < 0.001) [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 89%
“…This study enrolled 1191 Shiraz university employees and their spouses between the ages of 25 and 70 who were enlisted in a prospective cohort study in Shiraz (the capital of Fars province in southwest Iran) that began in 2018 and inducted 7643 participants (Shiraz Cohort Heart Study, SCHS) [ 25 , 26 ]. Additionally, 773 of 1191 participants were between 40 and 70 years old.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we applied QA-QC and Testing tools [ 34 ] to consider various possible components of related risk factors such as etiology of various clinical conditions, pathophysiology and numerous worldwide epidemiologic findings, that can lead to LVH in which increase in myocardial muscle mass based on ECG as a LVH diagnostic tool [ 1 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was a cross-sectional analysis of a prospective cohort which has been detailed elsewhere 30 31. In the current study, 7225 participants were screened against four different Mets definitions.…”
Section: Discussionmentioning
confidence: 99%